TEACHING READING COMPREHENSION THROUGH PLOT RELATIONSHIPS CHART STRATEGY - Linda Astuti Rangkuti; Wiki Tedi Rahmawati (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This article elaborates with teach reading comprehension through Plot Relationships Chart Strategy. Plot Relationships Chart Strategy helps students identify the major parts of a story and improves their comprehension. Comprehension is the main goal in reading process. Reading Comprehension is a process of making sense of written ideas through meaningful interpretation and interaction with language. This strategy provides students with a chart to help them comprehend the relationship among characters, goals, problems, and solutions. The chart has four columns; the first column is for the name of the characters, the second column is for the goals of the characters, the third column is for the problems or challenges that the characters faced, and the last column is for the solution of the problems. At last, this strategy helps students comprehend what they have read